IMPROVING FOOTBALL LEARNING OUTCOMES FOR SMA 13 BONE STUDENTS VIA METHOD PBL - Nur, Muhammad; Dos Santos, Hezron Alhim; Sutriawan, Agus; Dos Santos, Maria Herlinda (STKIP Muhammadiyah Kuningan, 2023)
The role of sport is becoming more and more important. Because sport not only plays a role in improving the physical fitness of a nation, but sport also plays a role in shaping human character, which in turn will bring glory to the name of a nation. All sports play an active role in Sisea, including takraw. The problem of coaching sepak takraw athletes is homework for sepak takraw coaches and coaches in South Sulawesi. The aim of this research is to determine the improvement in Sila Football Learning Outcomes through the Problem Based Learning Method. Using a type of classroom action research approach by taking research samples from SMA 13 Bone students and obtaining data from giving 2 cycles as well as the results of evaluations of the results of learning about soccer. In conclusion, motivation and seriousness in participating in the student learning process through the problem based learning learning model has proven to be effective and able to increase learning outcomes as well as student motivation and seriousness. This can be seen from the increase in student motivation and seriousness as well as the increase in soccer learning outcomes so that completion reaches 82% in the cycle second.